Dynamic contact guidance of myoblasts by feature size and reversible switching of substrate topography: orchestration of cell shape, orientation, and nematic ordering of actin cytoskeletons - Linke, Philipp; Tanaka, Motomu (Langmuir, 2019)
Biological cells in tissues alter their shapes, positions, and orientations in response to dynamic changes in their physical microenvironments. Here, we investigated the dynamic response of myoblast cells by fabricating substrates displaying microwrinkles that can reversibly change their direction within 60 s by axial compression and relaxation. To quantitatively assess the collective order of cells, we introduced the nematic order parameter of cells that takes not only the distribution of cell-wrinkle angles but also the degree of cell elongation into account. On the subcellular level, we also calculated the nematic order parameter of actin cytoskeletons that takes the rearrangement of actin filaments into consideration. The results obtained on substrates with different wrinkle wavelengths implied the presence of a characteristic wavelength beyond which the order parameters of both cells and actin cytoskeletons level off. Immunofluorescence labeling of vinculin showed that the focal adhesions were all concentrated on the peaks of wrinkles when the wavelength is below the characteristic value. On the other hand, we found focal adhesions on both the peaks and the troughs of wrinkles when the wavelength exceeds the characteristic level. The emergence of collective ordering of cytoskeletons and the adaptation of cell shapes and orientations were monitored by live cell imaging after the seeding of cells from suspensions. After the cells had reached the steady state, the orientation of wrinkles was abruptly changed by 90°. The dynamic response of myoblasts to the drastic change in surface topography was monitored, demonstrating the coordination of the shape and orientation of cells and the nematic ordering of actin cytoskeletons. The “dynamic” substrates established in this study can be used as a powerful tool in mechanobiology that helps us understand how cytoskeletons, cells, and cell ensembles respond to dynamic contact guidance cues.